2014
DOI: 10.5032/jae.2014.02184
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Safety Needs of Kentucky School-Based Agricultural Mechanics Teachers

Abstract: The frequency and severity of accidents that occur in the agricultural mechanics laboratory can be reduced when these facilities are managed by educators who are competent in the area of laboratory safety and facility management (McKim & Saucier, 2011). To ensure teachers are technically competent and prepared to manage an agricultural mechanics laboratory, teacher educators and state supervisory staff must provide a comprehensive preservice education and professional development opportunities in the area of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…It can be concluded that several agricultural mechanics laboratories in Iowa are in need of updating and renovation to make them meet today's safety regulations. Saucier et al (2014) suggested that without adequately sized and safe working conditions, agricultural mechanics laboratories may lead to more accidents and reduced learning opportunities for the students using them.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that several agricultural mechanics laboratories in Iowa are in need of updating and renovation to make them meet today's safety regulations. Saucier et al (2014) suggested that without adequately sized and safe working conditions, agricultural mechanics laboratories may lead to more accidents and reduced learning opportunities for the students using them.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…With budget constraints, programs are not able to keep adequate supplies on hand for experiential laboratory activities (Blackburn & Kelsey, 2012;Shinn, 1987;Sutphin, 1984). Saucier et al (2014) stated that working with a reduced budget may lead to the agricultural educator cutting out selected safety items or choose to use cheaper versions of safety equipment. This could lead to the teacher neglecting the laboratory resulting in a lower quality program (Newcomb et al, 2004).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As many SBAE programs have retained coursework in agricultural mechanics, teachers should be prepared to work safely and effectively in such environments to properly employ and maximize such resources (Saucier, Vincent, & Anderson, 2014). Pre-service teachers often feel challenged when stepping into the role of teaching agricultural mechanics content (Tummons, Langley, Reed, & Paul, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is reflected in early career teachers as well, as described by Burris, McLaughlin, McCulloch, Brashears, and Fraze (2010). Extensive research (Johnson & Schumacher, 1989;Johnson, Schumacher, & Stewart, 1990;McKim & Saucier, 2011a, 2011bSaucier & McKim, 2011;Saucier, McKim, & Tummons, 2012;Saucier et al, 2014; has been conducted to address in-service and pre-service teachers' laboratory management and safety education.…”
Section: Introductionmentioning
confidence: 99%